OP0056 IL-23P19 is up-regulated in monocyte-derived macrophages from HLA B27 positive patients with enthesitis related arthritis. (15th June 2017) - Fisher, C; Eleftheriou, D; Sen, D; Ioannou, Y
Abstract : Background: Enthesitis related arthritis (ERA) is an HLAB27-associated subtype of JIA most similar to the adult spondyloarthropathies (SpA). The innate immune system, intracellular stress response (the unfolded protein response (UPR)) and IL23/IL17 pathway are strongly implicated in the pathogenesis of adult SpA. However, these systems remain relatively unexplored in ERA. Objectives: To compare levels of the IL23 subunit, IL23p19, produced by monocyte-derived macrophages (MDMs) in the presence of lipopolysaccharide (LPS) and an inducer of the UPR (tunicamycin (TM)) from patients with ERA and healthy controls. Other pro-inflammatory cytokines and markers of the UPR were also studied. Methods: Peripheral blood monocytes isolated from 30 patients with ERA (20 HLAB27 positive, 10 HLAB27 negative, median age 16yrs 4mths, median disease duration 3yrs 9mths, M:F 7:1) and 16 age and gender-matched healthy controls were differentiated in vitro with macrophage-colony stimulating factor. Cells were treated with IFNγ and then stimulated with LPS alone or LPS with TM for 24 hours. Pro-inflammatory cytokines and markers of the UPR were measured by expression of mRNA using qPCR and normalised against GAPDH. Results: IL23p19 expression was higher in MDMs from HLAB27 positive patients with ERA compared to healthy controls treated with LPS [median relative expression 384.7 (IQR 179.2–1340) vs 90.5 (49.9–455.9), p=0.02]. With the addition of the UPR inducer, TM, enhanced IL23p19 mRNA expression was also seen in HLAB27 positive patients compared to those who were HLAB27 negative and healthy controls [median relative expression 608.9 (IQR 282–3286) vs 283.0 (IQR 20.1–928.2) vs 195.1 (IQR 9.8–853.7); p=0.02]. When the groups were divided in to males and females, significantly higher IL23p19 expression was seen in MDMs treated with LPS from male HLAB27 positive patients with ERA compared to male healthy controls [661.7 (IQR 169.7–1531) vs 78.3 (39.01–139.6), p=0.0095] (figure 1). This was also the case for MDMs treated with LPS and TM [537.5 (IQR 295.3–3054) vs 93.05 (IQR 2.7–1109); p=0.02]. To investigate the effect of UPR induction on IL23p19 mRNA expression, percentage increase was calculated for each patient between MDMs treated with LPS alone and MDMs treated with LPS and TM. Interestingly, median percentage increase for HLAB27 positive patients with ERA was 63% but a decrease was seen in IL23p19 mRNA expression for in HLAB27 negative patients (-3.8%) with the addition of TM. When HLAB27 positive patients not oh TNF inhibitors were compared to those on treatment, the median percentage increase between LPS and LPS + TM treated MDMs was significantly modulated [78.7% vs 10.1%, p-0.049]. mRNA expression for other pro-inflammatory cytokines including TNF, IL1 and IL6, in addition to markers of the UPR (XBP1, CHOP and BiP) demonstrated no significant differences between patients and healthy controls. Conclusions: Expression of IL23p19 mRNA in MDMs is significantly enhanced in HLAB27 positive patients with ERA. In this group, the induction of the UPR appears to further enhance IL23p19 expression but this effect is modulated by treatment with TNF inhibitors. These results suggest a potential role for IL23 and the UPR in the pathogenesis of ERA, particularly in those who are HLAB27 positive and may have implications for treatment stratification, indicating a subgroup of patients who may respond to IL23 blockade. Disclosure of Interest: None declared